Effect of Advertising on product growth of Techno Phone in Enugu State, Nigeria - Agu, Agu Okoro; Joy Nwakaego, Chris-Nnamchi; Uzonna, Ngwoke- Oliver (Journal of Research in Marketing (ISSN: 2292-9355), 2017)
The purpose of this seminar work is focuses on effect of advertising on product growth of techno phone in Enugu State, Nigeria. Specifically the study aimed to pursue the following objectives: to determine whether advertising increase sales of techno phone, to ascertain the effect of advertising on profit of techno phone, to determine the nature of the relationship between advertising and market share of techno phone. The study has a population /sample size of (25) using connivance sampling method at 5% error to tolerance and 95% level of confidence. Instruments used for data collection were primary questionnaires and interview. The total number of 25 copies of the questionnaire were distributed at a spot and collected . Survey research design was adopted for the study. Three hypotheses were tested using Pearson product moment correlation coefficient and simple linear regression tool. The findings indicate that advertising significantly increase sales volume of techno phone ( r = 0.616; F= 14.065; t = 3. 750; p< 0.05). Advertising significantly affect profit of techno phone (r = 0.651; F= 16.888 ; t = 4.110; p< 0.05). There is a positive relationship between advertising and market share of techno phone (r =.802, P<.05). The study concluded that effectiveness of advertising reach the target indexes of sales volume, market share, awareness and consumer preferences, i.e. achievement of all planned goals and objectives. The study recommends that organization should embark advertisement constantly, because it will help in educating their customers on how used their product and at same time increase the profit volume of the organization